BRANDING STRATEGY FOR RELIGIOUS DIVERSITY TOURISM VILLAGES BASED ON LOCAL WISDOM - Yulia Rahmawati; Rifma Ghulam Dzaljad; Titin Setiawati (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
Religious diversity is an important social capital in the development of tourism villages based on social and cultural values. Pulo Geulis Village in Bogor City, West Java, is known as a multi-ethnic and multi-religious area with a long history of tolerance practices in the daily lives of its residents. This article aims to analyze the branding strategy of the Religious Diversity Tolerance Tourism Village in Pulo Geulis Village, based on local wisdom, as an effort to build an inclusive and sustainable tourism destination identity. This research uses a qualitative approach with a case study method. Data collection was conducted through in-depth interviews with tourism village managers, religious leaders, community leaders, and local residents, as well as participant observation and analysis of tourism promotion documents. The results show that the branding strategy of Pulo Geulis Village is built through strengthening local historical narratives, cross-ethnic cultural symbols, practices of social tolerance among diverse communities, and participatory communication that actively involves the community in the tourism planning and promotion process. Branding tolerance is not only represented by visual and verbal promotional messages, but is also manifested as a social practice that lives in public spaces, tourism activities, and daily community interactions. These findings demonstrate that local wisdom plays a key role in building authentic, inclusive, and competitive tourism village branding. This study contributes to the development of community-based tourism communication studies and the strengthening of tolerance values ​​in sustainable tourism development in urban areas.